Steroidal and Potential Anti-inflammatory Properties of Carteriospongia sp from the Southeast Sulawesi Sea Coast - Daud, Nur Saadah; Yodha, Agung Wibawa Mahatva; Musdalipah, Musdalipah; Fusvita, Angriani; Firdayanti, Firdayanti; Sahidin, Sahidin; Arfan, Arfan; Fristiohady, Adryan; Sadarun, Baru (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2025)
Marine sponges are an abundant yet underutilized resource in Southeast Sulawesi, Indonesia, despite their ecological roles and pharmacological potential. Steroidal metabolites are dominant in many sponge species and have been widely recognized for their strong anti-inflammatory activity. However, the chemical composition and biological potential of Carteriospongia sp from Indonesian waters remain unexplored. Carteriospongia sp was extracted using the Soxhlet method, and the chemical profile was analyzed by Gas Chromatography–Mass Spectrophotometry (GC-MS). Anti-inflammatory activity was evaluated in vitro using the Bovine Serum Albumin (BSA) protein denaturation assay, with methylprednisolone as the positive control. Molecular docking studies were performed to assess the interactions between steroidal compounds and BSA protein. GC-MS analysis identified eight steroidal compounds such as 2-methylenecholestan-3-ol (S1), stigmasterol (S2), 4,4-dimethyl-cholesta-8,24-dien-3-ol (S3), 8,14-seco-3,19-epoxyandrostane-8,14-dione, 17-acetoxy-3ß-methoxy-4,4-dimethyl (S4), cholic acid ethyl ester (S5),  (3ß,5Z,7E)-9,10-secocholesta-5,7,10(19)-triene-3,24,25-triol (S6), stigmastan-3-en-6-ol (S7), ß-sitosterol (S8). The extract demonstrated concentration-dependent inhibition of protein denaturation, achieving 84.81% inhibition at 128 mg.L-1. The IC50 value was 3.71 mg.L-1, comparable to methylprednisolone (IC50 4.45 mg.L-1). Molecular docking revealed that compound S1 and S4 exhibited lower binding energies than other steroids, suggesting stronger stabilization of BSA protein. The findings demonstrate that Carteriospongia sp extract possesses significant anti-inflammatory potential, comparable to methylprednisolone. This study provides novel insights into the bioactive potential of Indonesian marine sponges and emphasizes the importance of further pharmacological and molecular studies to develop sponge-derived steroidal compounds as alternative or complementary anti-inflammatory therapeutics.